Acidity and Fatness in Milks from Machine Milking - Yildirim, S.; Cimen, M.; Bayril, T. (Asian Journal of Chemistry, 2010)
The objective of this research is to investigate the acidity and fatness in milk of machine milked cows. The data were obtained from 53 machine milked Holstein cows in early and late lactation period. The cows were fed with a total mixed ratio. The milk fat level of early lactation group was significantly lower compared to the late lactation group. The total solids and pH levels of cows did not differ between early lactation and late lactation groups. Milk components of cows were not affected by different lactation number (1 and 2).